The Effect of Economic Growth on The Absorption of Labor and Public Wellfare In Kediri City, East Java - Rachmiyati, Nekky; Kiak, Novi Theresia; Wiwoho, Bambang (Jurnal Ilmu Ekonomi Terapan, 2020)
The purpose of this study is to determine the effect of economic growth on labor absorption and community welfare in the city of Kediri, East Java in 2019. This research is a descriptive study and will supported by quantitative and qualitative data. Data consists of the number of Small and Medium Enterprises, types of business and work force to analyze the writer uses multiple linear regression method and the Location Quotient method. The R-square shows the influence given by the variable economic growth labor absorption on the welfare variable is 92.8%. The rest is influenced by other variables outside the regression equation. The LQ results are 2,612 with a dense population, so the business of trading and repairing cars and motorbikes is very developed and can serve the market in Kediri City, as well as outside Kediri City, second in Kediri City Information and Communication is the base and superior sector, this is indicated by an LQ of 2.107.